INTERAKSI ANTARA PELAYANAN PUBLIK DAN TINGKAT KORUPSI PADA LEMBAGA PERADILAN DI KOTA SEMARANG - Muhammad Shoim (Masalah-Masalah Hukum, 2011)
Including the judiciary of the 5 most corrupt institutions and institutions that have a public service of the worst that can be synthesized that there is a relauonship between public service corruption in public institutions. The results showed (1) the performance of public services is a good judiciary, however, differences occur in the public service performance of each of the judiciary (District Court, the Religious Courts, State Administrative Court) in the city, (2) the level of corruption of public institutions justice is sufficient, however, differences in levels of corruption occurs in each of the judiciary (District Court, the Religious Courts, State Administrative Court) in the city, and (3) public services and a significant negative impact on the level of corruption in the judiciary in the City Semarang means the better performance of public services the lower the level of corruption, and vice versa.